Biopolymer Nanocomposites for Sustainable UV Protective Packaging - Gore, Anil H.; Prajapat, Amrutlal L. (Frontiers in Materials, 2022)
Development of green, eco-friendly and sustainable packaging materials is a great challenge in the field of nanoscience and nanotechnology. Advancement in designing of biopolymeric nanocomposites for packaging applications have been established so far by considering their features like biodegradability, environmental friendliness, mechanical properties, cost, and safety etc. Alongside other properties like thickness, weight, transparency, practability, recyclability, antimicrobial, porosity, leaching effect, light protective capability etc. need to be considered during the fabrication of next generation packing materials for multifaceted applications. Among these, ultraviolet (UV) protective properties of the designed nanocomposites is utmost importance for sustainable packaging applications. UV protective properties of the packaging materials can be modulated through the addition of minute quantity of biocompatible nanomaterials having properties of maximum absorption in the UV region (200-400 nm). UV light absorption is very important to avoid loss or changes in intrinsic chemical, physical, biological properties/contents of foods, pharmaceuticals, beverages, etc. during storage and transportation. In current short review we have highlighted principle of UV light protection, selection of nanomaterials, designing of nanocomposite films, properties and applications of biopolymeric nanocomposite materials for UV protective sustainable packaging. Lastly, current challenges and prospects of sustainable UV protective packaging are also discussed to provide an insight into the future of next generation packaging technology.